OPTIMASI PORTOFOLIO CAPITAL ASSET PRICING MODEL (CAPM) PADA INDEKS BISNIS-27 - Aditya Fadillah Aridwianto; Dhelia Artasevia Artasevia; Najwa Mayang Vianisa; Syifa Gumay; Valentin Asman Lestari; Di Asih I Maruddani (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2025)
Stock efficiency analysis helps investors understand the intrinsic value of a stock and serves as a foundation for identifying risk factors and potential returns associated with it. This study evaluates stocks in the Business Index 27 from 22 Mei 2023 – 22 Mei 2024 by considering criteria such as positive returns, lowest correlation, and sectoral differences. Based on this evaluation, three stocks with efficient performance were selected: MEDC, BRPT, and JSMR. An optimal portfolio was formed by weighting these three stocks using the Capital Asset Pricing Model (CAPM) method, with weight proportions of MEDC at 23.3%, BRPT at 11.7%, and JSMR at 64.9%. Risk evaluation using the Historical Simulation method to calculate Value at Risk (VaR) indicates a potential loss of 10%. This study provides insights into identifying efficient stocks and forming an optimal portfolio, which can assist investors in making investment decisions in the Business Index 27.